2018
DOI: 10.1007/s00167-018-5305-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral fixation of meniscal allograft does not reduce coronal extrusion under physiological load

Abstract: Purpose Meniscal graft extrusion is a concern following meniscal allograft transplantation (MAT). MAT surgical techniques continue to evolve in an effort to reduce extrusion; however, improvements remain difficult to measure in vivo. A novel MRIcompatible in vitro loading device capable of applying physiologically relevant loads has been developed, allowing for the measurement of extrusion under a variety of controllable conditions. The objective of this study was to compare maximal medial MAT extrusion (1) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…16 Some authors have conducted imaging studies that correlate the grade of meniscal extrusion with the surgical technique, obtaining controversial results. 6,11,21,22 Koh et al 13 demonstrated instead that lateral MAT was significantly more extruded than medial MAT at 3 years’ follow-up; this difference might be related to differences in the anatomic restraints of the medial and lateral compartments.…”
Section: Discussionmentioning
confidence: 99%
“…16 Some authors have conducted imaging studies that correlate the grade of meniscal extrusion with the surgical technique, obtaining controversial results. 6,11,21,22 Koh et al 13 demonstrated instead that lateral MAT was significantly more extruded than medial MAT at 3 years’ follow-up; this difference might be related to differences in the anatomic restraints of the medial and lateral compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from a base load of 1 N, a repetitive load with a magnitude of 10 N was then applied 100 times (frequency, 1 Hz). A ground-reaction force of 200 N was applied to the distal tibia, 5,8 and scaled loads of 50 N and 20 N were applied to the quadriceps and hamstrings, respectively, at 30° and 60° of flexion (each angle of flexion was confirmed using a goniometer and defined as the angle formed between the anatomic axes of the femur and the tibia at their lateral aspects). The porcine knee cannot extend to 0°, beginning its range of motion at 30° of flexion.…”
Section: Methodsmentioning
confidence: 99%
“…So one of the goals of the technical improvements in MAT should be to decrease graft extrusion. Mid-body fixation of MAT to the tibia doesn't prevent extrusion under loading conditions [12]. Soft tissue fixation leads to a higher level of meniscal extrusion when compared to bone block fixation technique [3].…”
Section: Meniscal Extrusion Of Allograftsmentioning
confidence: 99%